Northwest Africa 10414, a pigeonite cumulate shergottite. (11th August 2019) - Hewins, R.H.; Zanda, B.; Pont, S.; Zanetta, P.‐M.
Abstract: Northwest Africa (NWA) 10414 is an unusual shergottite with a cumulate texture. It contains 73% coarse prismatic pigeonite, plus 18% interstitial maskelynite, 2% Si‐rich mesostasis, 2% merrillite, and minor chromite‐ulvöspinel. It contains no olivine, and only 3% augite. Phase compositions are pigeonite (En68‐43 Fs27‐48 Wo5‐15 ) and maskelynite An 54‐36, more sodic than most maskelynite in shergottites. Chromite‐ulvöspinel composition plots between the earliest and most fractionated spinel‐group minerals in olivine‐phyric shergottites. NWA 10414 mineralogically resembles the contact facies between Elephant Moraine 79001 lithologic units A and B, with abundant pigeonite phenocrysts, though it is coarser grained. Its most Mg‐rich pigeonite also has a similar composition to the earliest crystallized pyroxenes in several other shergottites, including Shergotty. The Shergotty intercumulus liquid composition crystallizes pigeonite with a similar composition range to NWA 10414 pigeonite, using PETROLOG. Olivine‐phyric shergottite NWA 6234, with a pure magma composition, produces an even better match to this pigeonite composition range, after olivine crystallization. These observations suggest that after the accumulation of olivine from an olivine‐phyric shergottite magma, the daughter liquid could precipitate pigeonite locally to form this pigeonite cumulate, before the crystallization of overlying liquid as a normal basaltic shergottite.